Pythium oligandrum in plant protection and growth promotion: Secretion of hydrolytic enzymes, elicitors and tryptamine as auxin precursor - Bělonožníková, Kateřina; Hýsková, Veronika; Chmelík, Josef; Kavan, Daniel; Čeřovská, Noemi; Ryšlavá, Helena (Microbiological research, 2022)
Pythium is a genus of parasitic oomycetes which target plants and both nonvertebrate and vertebrate animals, including fish and mammalian species. However, several Pythium spp., such as P. oligandrum, function as mycoparasites of pathogenic fungi, bacteria, and oomycetes in soil and thus as advantageous biocontrol agents. This review primarily focuses on biochemical processes underlying their positive effects. For example, P. oligandrum degrades host cell wall polysaccharides using chitinases, cellulases, endo-β-1,3-glucanases, and various exoglycosidases. Proteases from various classes also participate in the cell wall hydrolysis. All these processes can modify cell surface structures and help Pythium spp. compete for space and nutrition. Accordingly, enzyme secretion most likely plays a key role in plant root colonisation. Plant-P. oligandrum interactions, nevertheless, do not involve tissue injury but instead activate plant defence mechanisms, thereby strengthening future plant responses to pathogen attacks. Priming induces the phenylpropanoid and terpenoid pathways and thus synthesis of secondary metabolites, including lignin, for cell wall fortification and other metabolic adjustments. Such metabolic changes are mediated by elicitins, cell wall glycoproteins and oligandrins produced by P. oligandrum. As homologous proteins of β-cinnamomin from Phytophthora cinnamomi with similar essential amino acids for sterol binding, oligandrins stand out for their structure, which they share with cell wall glycoproteins, albeit without the Ser-Thr-rich O-glycosylated domain for cell wall attachment. P. oligandrum also provides plant with tryptamine used for auxin synthesis, promoting plant growth. Overall, in addition to discussing plant metabolic and phytohormonal changes after P. oligandrum inoculation, we review data on P. oligandrum applications as researchers increasingly search for effective and environmentally friendly ways to protect crops. In this context, P. oligandrum emerges as a highly suitable biotechnological solution.
Keywords: hydrolýza; Plant Diseases; Phytophthora; Oomycetes; tryptaminy; Sustainable agriculture; Biological control agents; Growth promotion; Pythium; Hydrolysis; Indoleacetic Acids; Tryptamines; Mycoparasitism; nemoci rostlin; kyseliny indoloctové; Plant protection